Employment Precarity Strengthens the Relationships Between the Dark Triad and Professional Commitment - Kaufmann, Leah M.; Wheeler, Melissa A.; Sojo, Victor E. (Frontiers in Psychology, 2021)
The Dark Triad traits of Machiavellianism, narcissism, and psychopathy have been found to negatively impact work behaviors including information sharing, reporting of unethical conduct, and mistreatment of colleagues and subordinates. However, research has found the Dark Triad can also be related to forms of organizational commitment which underpin positive work behaviors, including engaging in tasks and duties beyond those required (i.e., “going above and beyond”). Professional commitment is a broader form of commitment that has been found to be significantly related to organizational commitment, sharing antecedents, and having similar outcomes. Professional commitment, the affective, normative, and continuance commitment toward one's profession or occupation, has the benefit of applying to individuals employed by organizations as well as those working for themselves or between jobs. In this research, we explore relationships between professional commitment, using previous research on the relationship between the dark triad traits of Machiavellianism, psychopathy, and narcissism and organizational commitment, as a basis for predictions. We also explored two forms of precarious employment (career interruptions and part-time or casual work) as possible moderators of the dark triad-professional commitment relationship. Participants were 184 Australian professionals (52.2% men), a slight majority of whom had experienced a career interruption (69.6%) or a year or more of part-time or casual employment (70.7%). The results showed that psychopathy had a negative association with affective commitment, whereas Machiavellianism was positively related to normative commitment, and narcissism was positively related to normative and continuance commitment. Using regression analysis, we found that among individuals who have worked in part-time/casual employment longer, Machiavellianism and psychopathy had significantly stronger negative associations with affective commitment. In contrast, among individuals who have had a significant career interruption, Machiavellianism had significantly stronger positive association with continuance commitment. These findings help expand our understanding of both the dark triad and its contingent impact on workers' attachment to their profession.